Foreign manufecturing and changes in industry linkage patterns in Scotland and Wales - John Dewhurst; Max Munday; Annette Roberts (European Regional Science Association (ERSA), 2001)
Inward investment from foreign manufacturing firms has been sought as a remedy to regional industrial problems in the UK. Foreign manufacturing offers the prospect of industrial diversification, new jobs and incomes, and can also represent a stimulus to new ideas and practices in domestic industries. The potential for production externalities from the foreign to the domestic sector has been investigated in a number of empirical studies. The wider potential for foreign manufacturing to become a driver of regional competitive advantage is expected to be linked to a number of factors including underlying investment motives, subsidiary age and type, subsidiary size, degree of value added within the plant, type of plant/degree of autonomy, nationality of ownership, entry mode, industry sector, and the structure of the host/regional economy. An additional and inter-linked factor with the above is the extent to which foreign plants are embedded through their purchasing linkages into their respective local economies. The degree of embeddedness determines the indirect employment and output supported by foreign firm activities in regional economies, and is a general indicator of the extent to which foreign firms contribute towards regional growth. Previous research has work has highlighted the comparatively low levels of linkage that exist between inward investing sectors and local supply bases. For example, Turok (1993, 1997) demonstrated the Scottish electronics industry (including large numbers of inward investors) purchased just 12% of material inputs in Scotland, and that (with reference to Input-Output tables for Scotland) output based multipliers for the electronics sector still revealed a poor quality of linkages into the local economy. In Northern Ireland, Crone and Roper (1999) reported that weak supply linkages between foreign and regional firms had restricted the potential of positive production externalities. In Wales, Roberts (1996) considered the backward (and forward) linkages created by foreign manufacturing sectors in the local economy using 1994 Input-Output tables for Wales. Overall, this research found that, on average, less than 17% of non-wage spending of foreign manufacturing firms occurred in the Welsh economy (see also Gillespie, 2000). Finally, Brand, Hill and Munday (2000), explored in a regional Input-Output framework, the direct and indirect economic contribution of foreign owned and domestic manufacturing to the economies of Wales, Scotland and the West Midlands. The study demonstrated that foreign owned manufacturing in these regions purchased less locally than domestic firms. As a result in most of the industry sectors explored the output supported in other regional industries was generally greater in the domestic than in the foreign owned case. The analysis also explored how far each job created in foreign and domestically owned manufacturing contributed to regional value added. The superior productivity of the foreign sector meant that it generally contributed more per employee to regional value added than its domestic counterpart. The analysis of the impact of foreign (and in some cases domestic) manufacturing on local economies within an Input-Output framework has largely been based on cross-sectional information. The present paper attempts to develop a more dynamic perspective by considering structural changes over time. The objective of this paper is to explore the role of foreign manufacturing in changing the pattern of industry linkages in Wales and Scotland – two regions which have attracted comparatively high shares of new UK foreign inward investment. These two regions also make for a valuable comparative study with some analysts suggesting that there are important differences in the underlying quality of inward investment between the two regions (Hood, 1991). The paper uses information from the Scottish Input-Output tables 1973 and 1996 (see Fraser of Allander, 1973, and Scottish Executive, 1999), and Welsh Input-Output tables 1968 and 1996 (see Ireson and Tomkins, 1978; and Hill and Roberts, 2001) to examine the changing structure of these regional economies over time. The focus of the paper is comparing manufacturing sectors where there have been high and low levels of foreign investment. The influence of foreign manufacturing is considered in the context of changes in the export orientation, import propensity and indirect employment and output effects of selected industry sectors. The wider context of the paper is continuing concern in the UK on the more dynamic impacts of foreign manufacturing industry in improving the economic prospects for UK regions, and the validity of the `inward investment' model of development. The second section of the paper reviews the development of foreign manufacturing in the Welsh and Scottish economies, and critically analyses previous research that has explored the role of the foreign sector in these regions within an Input-Output model framework. The third section examines how foreign manufacturing might be expected to impact differently from the domestic sector in terms of impact on the structure of the regional economy over time. For example, in terms of its higher productivity, and different import and export propensities. The fourth section describes the Input-Output tables that are available for Wales and Scotland, and more specifically, discusses issues of comparability of tables of different vintages. The methodology used to reconcile the industry sectors in the table is discussed. The fifth section examines the nature of structural changes in the two economies, including an analysis of local trading propensities, together with estimates of multiplier effects of selected industries characterised by high and low levels of foreign direct investment (in the period 1968-1996 for Wales, and 1973-1996 for Scotland). The final section contains conclusions. References Hill, S. & A. Roberts (2001), Input-Output Tables for Wales 1996. Cardiff: South East Wales Economic Forum. Hood, N. (1991), Inward Investment and the Scottish Economy, Royal Bank of Scotland Review, 169, pp. 17-32. Brand S., Hill, S. & M. Munday (2000), Assessing the Impacts of Foreign Manufacturing on Regional Economies: The Cases of Wales, Scotland and West Midlands. Regional Studies 34, pp. 343-55. Crone, M. & S. Roper (1999), Knowledge Transfers from Multinational Plants in Northern Ireland, paper given to Regional Science Association European Congress, University College Dublin, August 23rd-27th. Fraser of Allander Institute, University of Strathclyde, The Scottish Council Research Institute Limited and IBM UK Scientific Centre (1978), Input-Output Tables for Scotland 1973. Scottish Academic Press, Edinburgh. Gillespie, G. (2000), Modelling the System-wide Impact of Foreign Direct Investment in Scotland: An Ownership-Disaggregated Regional Computable General Equilibrium Analysis, Ph.D thesis, University of Strathclyde. Ireson, R. & C. Tomkins (1978), Inter-Regional Input-Output Tables for Wales and the Rest of the UK 1968. HMSO, London. Roberts, A. (1996), The Economic Impact of Foreign Manufacturing Investment in Wales. Unpublished Ph.D, University of Wales, Cardiff. Scottish Executive (1999), Input-Output Tables and Multipliers for Scotland 1996. Government Statistical Service, Edinburgh. Turok, I. (1993), Inward Investment and Local Linkages: How Deeply Embedded is `Silicon Glen? Regional Studies 27, pp. 401-17. Turok, I. (1997), Linkages in the Scottish Electronics Industry: Further Evidence, Regional Studies 31, pp. 705-711.
Keywords: 330